Sujeito, narração e montagem: novos modos de representação no documentário latino-americano contemporâneo - Gálvez, Valeria Claudia Valenzuela (2008)
In an attempt to identify formal structures in contemporary Latin American documentary film production with which one can establish common production standards an analysis model was created enabling the identification of predominant discourse elements and editing figures in the works. In the documentary film by Latin American authors one notices an inner look which observes the historical world permeated by a subjective perception. The documentary filmmaker s look is evident in the film through the subject of enunciation who is part of the discourse in his role as author/character. This new contemporary audiovisual modality whose enunciation is manifested in I tell you the world is like this, expresses a process which brings together elements of a discourse which are apparently antagonistic: general and particular, individual and collective and political and personal. If Latin American documentary filmmakers of the Nuevo Cine created works that followed a didactic and passionate line; nowadays, their concerns cross a certain reflectiveness, presenting films of self-reference which deal with the reflective production process itself. A new language emerges as a practice in resistance which replaces what was once the revolutionary language: A narrative of affection , which with the record of the meeting between the filmmaker and the subject, which would be a political gesture as a unique point of reflection